A Comparative Analysis of Sino-US Humor Culture: Case Study of Ipartment and Friends - Jiamin, Wu; Li, Sun (International Journal of Culture and History, 2024)
Cultural shock is common due to cultural differences. Humor contains specific cultural connotations and has become an important tool to promote interpersonal communication. This paper compares and analyzes the differences of and reasons for Chinese and American humor culture by using sitcoms as examples. First, it describes the definition, classification, and characteristics of humor culture. Second, it compares the differences between Chinese and American verbal humor in the topic, target, and scene based on Chinese and American sitcoms Ipartment and Friends. Third, it analyzes the influence of historical origin, communication style and cultural value on the differences between Chinese and American verbal humor. Finally, three communication measures are proposed from the aspects of the context, empathy, and ethnocentrism to overcome intercultural communication barriers and promote Sino-American communication.